Confiding in ChatGPT? Emotional Communication Among Digital Agency Workers with Mobile-AI - Octafiani, Fanny; Wibowo, Octavianus Bima Archa; Irwansyah , Irwansyah (Riviera Publishing, 2025)
The study explores a new phenomenon in which digital agency workers express their emotions to ChatGPT, marking a shift in human–AI communication patterns. The purpose of this study is to understand how emotional interactions with AI are interpreted and experienced by users in the context of urban work. Using a phenomenological qualitative approach, data was collected through in-depth interviews with four informants who actively use ChatGPT in their professional and personal routines. The results show that ChatGPT is not only seen as a functional work tool, but also as an